Broadside: "Notice: Civilian Exclusion Order No. 102," 1942 (1942)
Poster/Broadside: "Notice: Civilian Exclusion Order No. 102,", June 30, 1942 posted in the Presidio of San Francisco for all of the counties of Alpine and Mono and part of the counties of Placer, Eldorado, Amador, Calaveras, Tuolumne, Mariposa, and Madera within California.